How Can Eastern/Southern Mediterranean Countries Resolve Quality and Safety Issues in Transfusion Medicine? - Haddad, Antoine; Bou Assi, Tarek; Garraud, Olivier (Frontiers in Medicine, 2018)
Unlike their Western counterparts, some of the Eastern/Southern Mediterranean countries lack centralized coordinated blood transfusion services leading to an unequal blood safety level. This was recently highlighted by a recent World Health Organization (WHO) regional committee report in which WHO urges these countries to establish and implement a national blood system with well-coordinated blood transfusion activities and to make attempts to reach 100% voluntary non-remunerated blood donation. The objective is thus to meet the same levels or standards as Western countries in term of self-sufficiency and blood safety. This raises the question whether these countries can either comply with Western countries’ guidelines and experiences or develop their own safety scheme based on proper sociopolitical and economic features. Another option is to identify efficient and cost-effective strategies setup successfully in neighbor countries sharing cultural and economic features. To address this issue—and make an attempt to achieve this goal—we designed a number of surveys specifically addressed to Mediterranean countries, which were sent out to the national authorities; so far, five surveys aim at covering all aspects in blood collection, processing, testing, inventory and distribution, as well as patient immune-hematological testing and follow-up (including surveillance and vigilances). It is anticipated that such practice can help identifying and then sharing the more successful and cost-effective experiences, and be really focused on Mediterranean areas while not necessarily copying and pasting experiences designed for Western/Northern areas with significantly distinct situations.